A conceptual approach for understanding computer programming skills development - Md Ali, Asma; Tumian, Afidalina; Abu Seman, Muhamad Sadry (IEEE, 2017)
This paper highlights the relevant curricular and pedagogical ideas on how to evaluate students in learning computer programming. It explores the literature in the area of programming skills development towards constructive alignment in outcome-based education. Research on teaching computer programming has led to numerous practices, instructional theories, and empirical results for computer science pedagogy. The change towards constructivism seems promising in establishing a systematic computer programming skills development in the future. Three main areas that affect students learning computer programming are teaching approach, computer programming language selection, and programming development environment. The outcome of this paper is a conceptual approach that covers (1) the teaching and learning alignment as unit of analysis (2) a holistic approach on how programming skills are developed, (3) an emphasis on activities and (4) the importance of providing guidelines for lecturers.